Pengaruh Influencer, Content Marketing Dan Customer Experience Terhadap Purchase Intention Pada Brand Roughneck 1991 (Studi Kasus Pada Mahasiswa Feb Unisma) - Muh. Fadel Akbar Sukarno; Agus Widarko; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine the effect of Influencer, Content Marketing and Customer Experience to Purchase Intention on Brand Roughneck 1991 variable for FEB students at the Islamic University of Malang. The type of research used is quantitative research with questionnaire distribution method. The sample in this study were 90 respondents and data processing using the SPSS computer program. This study has met the requirements of validity and reliability. The data analysis used in this study is the classical assumption test, multiple linear regression, hypothesis testing and coefficient of determination analysis. The variables used in this study are the Purchase Intention (the dependent variable), while the independent variables are Influencer, Content Marketing and Customer Experience. The results of this study conclude that the variables of Influencer, Content Marketing and Customer Experience have an effect both simultaneously and partially on Purchase Intention. The results of this study conclude that the variables of Influencer, Content Marketing and Customer Experience have an effect both simultaneously and partially on Purchase Intention. Keywords : Influencer, Content Marketing, Customer Experience, Purchase Intention